MANAJEMEN INSANI QURANIK: PANDUAN PENGELOLAAN SUMBER DAYA MANUSIA - Desi Safitri; Ari Daryani (Almarhalah: Jurnal Pendidikan Islam, 2023)
Humans, as creations of Allah SWT, possess unique abilities and hold a preeminent status among all living beings. The Quran elucidates that humans are designated as stewards on Earth. In the Hadith of the Prophet Muhammad SAW, it is emphasized that a virtuous individual should exhibit abundant kindness towards their fellow human beings. Human potential can be categorized into physical and spiritual dimensions. Allah SWT fashioned humans to be recipients and practitioners of His teachings, elevating them to an honorable position. These potentials granted to humans fundamentally represent Allah SWT's guidance (hidayah) to enable them to lead lives harmonious with their inherent nature. In the context of Islam, human resource management aligns with the model exemplified by the Prophet Muhammad SAW, grounded in the Islamic conception of humanity. The primary tenets are as follows: 1. Humans are created to worship God, implying that all human endeavors should manifest as acts of worship. 2. Humans serve as vicegerents of Allah on Earth, responsible for its stewardship. The overarching objective of human resource management is to optimize productivity within an organization. Human resources are a sacred trust that demands conscientious stewardship, which holds significance in the afterlife. Thus, effective human resource management should be guided by Islamic Sharia, as illuminated in the Quran, which offers explicit guidance on the management of human resources.